2005
DOI: 10.1086/499561
|View full text |Cite
|
Sign up to set email alerts
|

The Dust Cloud around the White Dwarf G29-38

Abstract: We present new observations of the white dwarf G29-38 with the camera (4.5 and 8 mm), photometer (24 mm), and spectrograph (5.5-14 mm) of the Spitzer Space Telescope. This star has an exceptionally large infrared excess, amounting to 3% of the bolometric luminosity. The spectral energy distribution (SED) has a continuum peak around 4.5 mm and a 9-11 mm emission feature 1.25 times brighter than the continuum. A mixture of amorphous olivine and a small amount of forsterite in an emitting region 1-5 from the star… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
230
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(240 citation statements)
references
References 32 publications
9
230
1
Order By: Relevance
“…The collective properties of all published (N ∼ 250 as of this writing), metal-polluted white dwarfs support the accretion of planetary debris for the population at large Farihi et al 2010a;Zuckerman et al 2003), including even those stars that do not exhibit detectable infrared excesses (Rocchetto et al 2014). These findings imply that at least 30% (Koester (Farihi et al 2008;Reach et al 2005). Also listed are 3σ upper limits from MIPS 70 µm photometry (Jura et al 2009b), and the similar PACS and ALMA limits reported here.…”
Section: Tidally-destroyed Planetesimalssupporting
confidence: 84%
See 1 more Smart Citation
“…The collective properties of all published (N ∼ 250 as of this writing), metal-polluted white dwarfs support the accretion of planetary debris for the population at large Farihi et al 2010a;Zuckerman et al 2003), including even those stars that do not exhibit detectable infrared excesses (Rocchetto et al 2014). These findings imply that at least 30% (Koester (Farihi et al 2008;Reach et al 2005). Also listed are 3σ upper limits from MIPS 70 µm photometry (Jura et al 2009b), and the similar PACS and ALMA limits reported here.…”
Section: Tidally-destroyed Planetesimalssupporting
confidence: 84%
“…All dusty white dwarfs observed with IRS on Spitzer exhibit strong silicate emission features consistent with olivines, (Jura et al 2009a;Reach et al 2009;Lisse et al 2008;Reach et al 2005), and which are also seen in the infrared spectra of evolved solids associated with planet formation (Lisse et al 2008).…”
Section: Tidally-destroyed Planetesimalsmentioning
confidence: 82%
“…First are the strong silicate emission features (Reach et al, 2005a;Jura et al, 2007b). In fact, the emission observed at GD 362 is among the strongest silicate features seen towards any mature star (compare e.g.…”
Section: Basic Dust Propertiesmentioning
confidence: 99%
“…Within the first two cycles of Spitzer observations, the only two known white dwarfs with circumstellar dust (G29-38 and GD 362 4 ) were observed with all three cryogenic instruments (Reach et al, 2005a;Jura et al, 2007b). The Infrared Array Camera (IRAC; Fazio et al 2004) obtained photometry at 3.6, 4.5, 5.7, and 7.9 µm, the Infrared Spectrograph (IRS; Houck et al 2004) acquired R ∼ 100 spectra between 5 and 15 µm, and the Multi-band Imaging Photometer for Spitzer (MIPS; Rieke et al 2004) measured fluxes at 24 µm for the two earliest examples shown in Figure 3, and later for a number of similar white dwarf targets prior to the loss of cryogen in 2009.…”
Section: Basic Dust Propertiesmentioning
confidence: 99%
See 1 more Smart Citation